Feeding guests by the family members of a deceased person: an Islamic jurisprudential analysis - Jamaludin, Khairul Fahmi; Zakaria, Mohamad Sabri; Abdullah, Mohamad Asmadi; Abas, Afridah (Serials Publication (P) LTD, 2020)
Among the practice that has been accustomed in the Muslim community of the Nusantara region is feeding the guest who pays a visit to their house. This is done as an act of showing their gratitude for the guest visiting them who brings blessing (barakah) to their home. This practice also extends to the event when someone has passed away. The family members of the deceased person (mayyit) will feed the guests who gather at their house on the night of the funeral ceremony. In reality, this practice is not only done to show appreciation for the visit but also to express their gratitude to the guest for reciting Quran, as well as offering the reward of the previous acts to their family member who has just passed away. However, the family members are prohibited from utilising any money from the inheritance of the deceased in doing so. There must be an assurance that the expenses to organise such ceremony or event are not taken from the inheritance either in the form of money or property of the children of the deceased person. Otherwise, such ceremony will be considered as misuse of the property of the children. This act, in particular, will affect the essence of feeding guests to the point that it will alter the ?ukm of this act from permissibility into muharramah (prohibited) act. Recently, this practice has become the main target of certain groups who consider it as wailing (niyahah) that would tantamount to innovation (bid’ah) in religion. This paper aims to study the methodology of ijtihad used by Nusantara scholars as well as the sources of Islamic law they referred to in allowing the practice of feeding the guest. This paper reveals that Nusantara scholars use various turuq of istinbat while referring to various sources of Islamic law that consist of primary and secondary sources. It is hoped that this paper gives a better understanding of the methodology of ijtihad used to arrive at the conclusion that this practice is allowed in Islam.